‘A Tale of Two Cities’ - Nationalism in Zion and Babylon - Sheriffs, Deryck C. T. (1988)
Studying Babylonian and Old Testament nationalisms challenges scholars to study the ideologies of their own cultures, and in turn to address them in terms which communicate God's message today.
Keywords: zion; Nationalism; Old Testament; Babylon